PENGARUH MANAJEMENT TALENTA TERHADAP KINERJA KARYAWAN MELALUI RETENSI KARYAWAN PADA PD. BPR BANK DAERAH LAMONGAN - AULA RAHMAWATI, HANUM (Jurnal Ilmu Manajemen (JIM), 2018)
Human resources are the main factor that must be considered in the effort to maintain and develop the company. This study aims to examine and influence the talent management on employee performance through employee retention in PD. BPR Lamongan Regional Bank. This study uses a quantitative approach obtained by observation, interviews and distributing questionnaires. The sample used in this study amounted to 79 employees in PD. BPR Lamongan Regional Bank obtained using stratified sampling technique. Data analysis was performed using Partial Least Square (PLS) analysis techniques with SmartPLS 3.0. The results of this study indicate that talent management has a significant positive effect on employee performance, talent management has a significant positive effect on employee retention, employee retention has a significant positive effect on employee performance and talent management has a significant positive effect on employee performance through retention in PD. BPR Regional Bank of Lamongan. Keywords: employee performance; employee retention; talent management